(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
This article provides a brief overview of the Indian public sector, and discusses changes ingovernment policy toward the public sector. This essay also addresses some disinvestment-relatedquestions, including why, how much, and how to implement disinvestment, as well as its conclusion